A Liquid Chromatography-Tandem Mass Spectrometry Method for Evaluation of Two Brands of Enalapril 20 mg Tablets in Healthy Human Volunteers - Wael Abu Dayyih; Mohammed Hamad; Ahmad Abu Awwad; Eyad Mallah; Zainab Zakarya; Alice Abu Dayyih; Tawfiq Arafat (Journal of Analytical Methods in Chemistry)
Enalapril is an angiotensin-converting enzyme inhibitor used for treatment of hypertension and chronic heart disease. Enalaprilat is its active metabolite responsible for the activity. This study aimed to develop and validate a method for enalapril and enalaprilat analysis and to determine the bioequivalence of two tablet formulae of enalapril. LC-MS/MS bioanalytical method was developed and validated and then applied to evaluate the bioavailability of two enalapril formulae. Antihyperglycemic sitagliptin was used as internal standard (IS). The method was accurate for the within- and between-days analysis, and precise CV% was <5%, being linear over the calibration range 1.0–200.0 ng/ml. Stability was >85% and the LOD was 0.907 and 0.910 ng/ml for enalapril and enalaprilat, respectively, and LLOQ was 1 ng/ml. The pharmacokinetic parameters Cmax, tmax, AUC0–72, and AUC0–∞ values of enalapril and enalaprilat of the two formulae were calculated and nonsignificant differences were found. A linearity, specific, accurate, and precise method was developed and applied for the analysis of enalapril and enalaprilat in human plasma after oral administration of two formulae of enalapril 20 mg tablets in healthy volunteers. Depending on the statistical analysis it was concluded that the two enalapril formulae were bioequivalent.